GRAVIMETRIC ANALYSIS OF URBAN SOLID WASTE FROM A SANITARY LANDFILL - Lima, P. G.; Destro, G. E.; Braga Junior, S. S.; Forti, J. C. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The urban solid waste presents quite different constituents in its production and volume and is related to specific factors of each region, such as climate, consumption pattern, lifestyle, the degree of urbanization and industrialization. The influence of these factors determines the physical characteristics of the waste produced by a given municipality. This study aimed to characterize urban solid waste deposited in a sanitary landfill of a municipality in the interior of the State of São Paulo to understand the consumption profile and the economic potentialities present in this solid waste. For this, a study of the gravimetric composition was carried out to know the various components that constitute the urban solid waste deposited in the sanitary landfill of the municipality under study. The results of this analysis showed that 72.94% of the residues deposited in the sanitary landfill have a potential for other economic activities, such as composting, for presenting a large mass of organic waste (44.89%), and recycling/reuse. Considering the economic potential of the recycling fraction, the results showed that the waste that is discarded could generate an income of approximately R$ 2,700.00 per month, which for municipalities with the same profile, this income would be contributing to the income of at least two families who work with the recycling of materials.